Impact of micro irrigation on groundwater savings, productivity, and profitability of principal crops in the Eastern Dry Zone and Central Dry Zone of Karnataka: a resource economic analysis - N Nagaraj; S Anitha (Agricultural Economics Research Review, 2023)
This study aims at estimating the cost of irrigation and its implications on water savings, productivity, net returns, and relative profitability. The study finds that irrigation cost forms a sizeable proportion of the total cost of production in both flow irrigation and micro irrigation systems. The economic analysis indicates that the crops considered are profitable—as reflected in the net returns realized, with and without irrigation cost—but upon accounting for the irrigation cost with externalities we see a sharp fall in net returns for all the crops. Nevertheless, micro irrigation enabled water savings, and it enhanced productivity and relative profitability.